Tlingit Indians paddling canoes in Yakutat Bay, Alaska, 1902. - Meany, Edmond S. (Edmond Stephen), 1862-1935
People are paddling canoes, carrying goods. In Meany Album v.1, p.49 Caption in Album: Yakutat. Indians coming out with baskets.